A Study on the Relationship between Attachment Styles of School Children Aged 5 â 6 and Personality Traits of Their Mothers - GÃƒÂ¶rgÃƒÂ¼, Ertan; Ural, Ozana (Social Science Learning Education Journal, 2017)
This research aims to investigate the association between attachment styles of school children aged 5-6 and personality traits of their mothers. Designed in accordance with the relational screening model, the study group of the research consisted of 160 mothers and their children (84 girls, 76 boys; 74 five years old, 86 six years old) who agreed to participate in the survey from the districts of EyÃ¼p, BeÅiktaÅ and BeyoÄlu in European side of Istanbul province. The data were collected from 6 different schools.